HAK ATAS PENDIDIKAN BAGI PENGUNGSI DI INDONESIA: The Right to Education for Refugees in Indonesia - Bagas Raysan Azharsyah; Maya Indrasti Notoprayitno (Faculty of Law, Universitas Trisakti, 2025)
Indonesia has become a refuge for a large number of refugees coming from various countries, both located in the Asian region and from other parts of the world. The purpose of this paper is to describe the right to education for refugees, focusing on the situation of Rohingya refugees in Indonesia. Refugees from the Rohingya community face major challenges in accessing education, such as unclear legal status, limited facilities and language barriers. The issue is how the Government of Indonesia, which is not a state party to the 1951 Refugee Status Convention, can provide the right to education for refugees. This research is a normative legal research, which aims to review and analyze legal regulations governing refugee rights, especially the right to education for refugees in Indonesia. The result and conclusion; the Indonesian government has issued policies that support the right to education including for refugees, however, more effective and comprehensive implementation is still needed. The government and relevant institutions must strengthen coordination and provide education that is affordable, comprehensive, and responsive to refugees' needs.